2014
DOI: 10.1111/ijfs.12527
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of oil extraction from sardine (Sardina pilchardus) by hydraulic pressing

Abstract: Summary The aim of this study was to evaluate the influence of the processing conditions (pretreatment temperature: 5–55 °C, pressure: 60–120 bar and number of pressing stages: 1–3) on the yield and quality (free fatty acids, peroxide value, p‐anisidine and Rancimat induction period) of the oil extracted from whole sardine by hydraulic pressing. Experimental factors were investigated by a designed experiment and optimised by response surface methodology. A maximum yield of oil, 12.47%, was obtained at 55 °C, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…However, the deodorization of the bleached samples carried out by distillation significantly increased the samples PVs from 2.21 meq to 4.55 meq O 2 /kg in case of sardine oil and from 2.88 to 3.78 meq O 2 /kg in case of sardine by‐product oil (Table ). Despite this increase of the PVs, the obtained values are still lower than those reported by García‐Moreno et al (from 0.33 to 5.74 meq O 2 /kg) and Chakraborty and Joseph (from 3.62 to 8.25 meq O 2 /kg). As already mentioned, the reason for this can be found in differences between used raw materials, their manipulation, and storage until processing as well as the applied refinement procedures.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…However, the deodorization of the bleached samples carried out by distillation significantly increased the samples PVs from 2.21 meq to 4.55 meq O 2 /kg in case of sardine oil and from 2.88 to 3.78 meq O 2 /kg in case of sardine by‐product oil (Table ). Despite this increase of the PVs, the obtained values are still lower than those reported by García‐Moreno et al (from 0.33 to 5.74 meq O 2 /kg) and Chakraborty and Joseph (from 3.62 to 8.25 meq O 2 /kg). As already mentioned, the reason for this can be found in differences between used raw materials, their manipulation, and storage until processing as well as the applied refinement procedures.…”
Section: Resultscontrasting
confidence: 71%
“…It is well known that these processes are usually more intense in the post‐mortem period of small pelagic fish . However, García‐Moreno et al obtained the lowest FFA values in oils extracted at the highest processing temperature and this has been explained by the fact that at temperatures above 45 °C, lipases from sardines become unstable. As the temperature applied in our study was significantly higher, this could also explain the low FFAs content of the investigated oils.…”
Section: Resultsmentioning
confidence: 99%
“…This result confirms the idea that palmitic acid is the main saturated fatty acid (SFA) in many saltwater species, accounting for about 70% of the total SFAs (Özogul et al ., ), and also corroborates the results obtained by García‐Moreno et al . (), who observed that palmitic acid was also highly present in the gross oil of whole sardines (20% of the total amount of SFAs) ( Sardina pilchardus ) extracted with the hydraulic pressing method. Fatty acid profile similar to that obtained by the IO was observed by Eom et al .…”
Section: Resultsmentioning
confidence: 99%
“…Fish oil is the most important source of polyunsaturated fatty acids (PUFAs), especially the omega-3 fatty acids eicosapentaenoic acid (C20:5n-3-EPA) and docosahexaenoic acid (C22:6n-3-DHA), both of which play a beneficial role in human health. The benefits related to intake of EPA and DHA fatty acids have attracted increased interest over recent decades by the pharmaceutical and food industries (Garc ıa- Moreno et al, 2014). Therefore, the production of fish oil rich in PUFAs is a good opportunity to add value to fish by-products and increases the competitiveness of the fishing industry (Rubio-Rodr ıguez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation